2020
DOI: 10.11646/zootaxa.4845.2.11
|View full text |Cite
|
Sign up to set email alerts
|

The genus Microhyla (Anura: Microhylidae) in Pakistan: species status and origins

Abstract: The territory of Pakistan has been influenced by biota from different geographic directions, and is divided zoogeographically into the Palearctic and Oriental regions (Khan 2006; Masroor 2012). This makes Pakistan one of the important territories in Eurasia in the understanding of past biodiversity dynamics. Well-known examples of Oriental elements among its amphibian fauna are observed in all four families of toads and frogs currently known from Pakistan: Bufonidae, Microhylidae, Megophryidae, and Dicroglossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Our results are in agreement with Howlader et al (2015a), who reported genetic divergence of M. nilphamariensis with its congeners (5.7% to 13.2%). In a recent study, Jablonski et al (2020) Kerala (Garg et al, 2018(Garg et al, , 2019Howlader et al, 2015a;Khatiwada et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our results are in agreement with Howlader et al (2015a), who reported genetic divergence of M. nilphamariensis with its congeners (5.7% to 13.2%). In a recent study, Jablonski et al (2020) Kerala (Garg et al, 2018(Garg et al, , 2019Howlader et al, 2015a;Khatiwada et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…also revealed the species status of the genus from Pakistan (Islamabad and Northern Punjab) and reported the populations from the country as M. nilphamariensis.Based on recent studies ofGarg et al (2019) andGorin et al (2020),Jablonski et al (2020) also reported the absence of M. ornata from Pakistan. Microhyla nilphamariensis species can also be morphologically characterized based on its dark brown diamond-shaped marking on dorsal side, dark streak from back of eyes to shoulders, lateral bands from tip of snout to the groin on either side of the body, blackish-brown mottling on throat, chest and margins of the belly, and indistinct inner metacarpal and metatarsal tubercles(Howlader et al, 2015a).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Pakistan is a country in the transition zone between the Palearctic and Oriental faunas, which is based on the fact that representatives of (not only) amphibians from both these two zoogeographic regions may be found in the country (Khan 2006;Jablonski et al 2020Jablonski et al , 2021. Currently, the territory of Pakistan contains four families of amphibians: Bufonidae Gray, 1825; Dicroglossidae Anderson, 1871;Megophryidae Bonaparte, 1850;andMicrohylidae Günther, 1858 (Masroor 2012;Sarwar et al 2016;Frost 2021).…”
Section: Introductionmentioning
confidence: 99%